The Segregation of Migrant Students in Schools in Santiago, Chile [Segregación Escolar de Estudiantes Migrantes en Escuelas de Santiago, Chile] - Cordoba-Calquin, C (Pontificia Universidad Javeriana, 2022)
The Chilean school system gradually teaches migrant students who usually attend public schools and are clustered in some institutions which, in Santiago, are located in the central communes district. This phenomenon is usually explained by the residential pattern of the students, a hypothesis which this study analyzes. It took the form of a comparative case study, of a quantitative and longitudinal nature, which took advantage of data (for the period from 2006 to 2018), on schools which have a large number of foreign students and neighboring schools which do not. It concludes that neither the residential pattern nor the administrative structure explains the phenomenon. Nor did it find evidence to suggest that Chilean students leave schools with many foreign students. © 2022 Authors. All rights reserved.